Nontraumatic Exertional Fatalities in Football Players, Part 2: Excess in Conditioning Kills. Issue 8 (19th August 2020) - Boden, Barry P.; Fine, Ken M.; Spencer, Tiahna A.; Breit, Ilan; Anderson, Scott A.
Background: The incidence of nontraumatic fatalities in high school (HS) and National Collegiate Athletic Association (NCAA) football players has continued at a constant rate since the 1960s. Purpose: To describe the causes of nontraumatic fatalities in HS and NCAA football players and provide prevention strategies. Study Design: Descriptive epidemiology study. Methods: We reviewed 187 fatalities in HS and NCAA nontraumatic football players catalogued by the National Registry of Catastrophic Sports Injuries during a 20-year period between July 1998 and June 2018. Results: The majority (n = 162; 86.6%) of fatalities occurred during a practice or conditioning session. Most fatalities, when timing was known, (n = 126; 70.6%) occurred outside of the regular playing season, with the highest incidence in the August preseason (n = 64; 34.2%). All documented conditioning sessions were supervised by a coach (n = 92) or strength and conditioning coach (n = 40). The exercise regimen at the time of the fatality involved high-intensity aerobic training in 94.7%. Punishment was identified as the intent in 36 fatalities. The average body mass index of the athletes was 32.6 kg/m 2 . For athletes who died due to exertional heat stroke, the average body mass index was 36.4 kg/m 2, and 97.1% were linemen. Conclusion: Most nontraumatic fatalities in HS and NCAA football players occurred during coach-supervised conditioning sessions. The primary cause of exertion-related fatalities was high-intensity aerobic workouts that might have been intended as punishment and/or excess repetitions. Exertion-related fatalities are potentially preventable by applying standards in workout design, holding coaches accountable, and ensuring compliance with the athlete's health and current welfare policies.